Engineering multiple-domain forms of the therapeutic antibody CAMPATH-1H: effects on complement lysis. - Greenwood, J; Gorman, S; Routledge, E; Lloyd, I; Waldmann, H (1994)
Antibody-mediated lysis of cells involves a complex interaction between the cell, the target antigen, the antibody and host effector mechanisms. One such mechanism, complement-mediated cell lysis, requires the interaction of C1q with the antibody heavy chain constant regions, and in particular the CH2 domain. Here we investigate the potential benefit of multiple-domain forms of the therapeutic monoclonal antibody CAMPATH-1H. This antibody is directed against the CDw52 antigen expressed by human lymphocytes and has proven lytic abilities both in vitro and in vivo. Using target cells with either high or low antigen density, engineered antibodies that contained additional domains in tandem (CH2, hinge-CH2 or Fc intramolecular repeats) showed no improvement in complement-mediated lysis when compared with controls. However, a homodimeric form of the antibody that was engineered by mutation of a serine residue to cysteine near the carboxy-terminal of the CH3 domain, exhibited markedly improved lysis using target cells expressing antigen at low density. Interestingly, no improvement was seen using cells expressing antigen at high density. These results suggest that dimeric forms of antibodies could be useful for converting cells with low density antigens into useful targets for therapy.